Synthesis Of Paramagnetic Merkapto Silica Hybrid From Rice Husk Ash For Ag(I) Adsorben - Saral Dwi Miftiyati; Saprini Hamdiani; Made Ganesh Darmayanti (Chemistry Education Program, the University of Mataram, 2018)
A study has been conducted on the synthesis of paramagnetic mercapto silica hybrids as metal adsorbent of Ag(I). The aim of this study was to synthesis paramagnetic mercapto silica hybrid from rice husk ash waste, knowing the characteristics of paramagnetic mercapto silica hybrid from rice husk ash waste, and to determine the effect of pH, metal ions concentration, and the contact time on the value of adsorption capacity (Q). Based on the results of the study, it was found that paramagnetic mercapto silica hybrids can be synthesized from the rice husk ash waste. Characterization using FTIR spectroscopy showed that silanol (Si-OH), siloxan (Si-O-Si), -SH, and Fe-OH functional groups, and characterization of paramagnetic mercapto silica hybrid structures using XRD to show crystalline compounds with a position value of 2Î¸ = 35.4 which showed that the magnetite material of Fe3O4 was coated by silica. Paramagnetic mercapto silica hybrids from rice husk waste can be used as adsorbent of Ag (I) metal at optimum conditions of pH 3, contact time of 120 minutes, and adsorption capacity of 392.01 mg/g. The suitable isotherm model is the Freundlich isotherm model which means the absorption of metal Ag (I) occurs physically, while adsorption of kinetics followed the pseudo II order kinetic model with a value of k = 3.01 g.mg-1 minute-1.